ANALYSIS OF AMBIENT AIR QUALITY AND GENSET EMISSIONS AT PT. REKSO NASIONAL FOOD (MC. DONALDS) GORONTALO CITY - Ekawaty Prasetya; Andi Makkulawu (UNG, 2023)
Air, as one of the components of the environment, is the most essential requirement in supporting life. Metabolism in the bodies of living things cannot occur without air oxygen. Air can be grouped into outdoor air and indoor air. Indoor air quality dramatically affects human health because almost 90% of human life is indoors. Indoor air quality is a problem that needs attention because it will affect human health. The emergence of poor indoor air quality is generally caused by several things, namely lack of air ventilation (52%), sources of indoor pollution (16%), outdoor pollution (10%), microbes (5%), and building materials (4 %). ), others (13%). Sources of air pollution can also come from household activities, starting from the kitchen in the form of smoke. According to several studies, air pollution from kitchens contributes significantly to ARI. The novelty of this research is that it examines ambient air quality and generator emissions. The study aimed to analyze Ambient Air Quality and Generator Emissions at PT Rekso National Foods (MC Donalds) in Gorontalo City. The results showed that the surrounding air quality still met the requirements, both CO, TSP, PM10, PM 2.5 and generator emissions. However, the noise factor still does not meet the threshold standard. This study concludes that all variables still meet predetermined threshold values except for the noise variable, which exceeds the threshold value.